Academic Leadership And Organizational Commitment In Public Universities Of Malaysia - Asaari, Muhammad Hasmi Abu Hassan; Dwivedi, Ashish; Lawton, Alan; Desa, Nasina Mat (Universiti Sains Malaysia, 2016)
The purpose of this paper is to examine the relationship between academic leadersip and organisational commitment. The independent variable, academic leadership, is formed by visionary, adaptable to change, competency, effective leadership, transformational style, and charisma while the dependent variable is organisational commitment. A total of 251 questionnaires were obained from faculty members of public universities in Malaysia, which yielded a response rate of 41.8%. The results reveal that academic leadership, namely adaptable to change, transformational style andcharisma, are significantly and positively related to organisational commitment. Theoretically, this paper contributes to the literature onacademic leadership and organizational commitment. Practically, top management of public universities should consider trainings and courses on change, transformation, and charisma that boost academic leadership of faculty members. In conclusion, this paper reveals the importance of change, transformation, and charisma as factors of academic leadership in affecting organisational commitment of faculty members of public universities in Malaysia.